2002
DOI: 10.1046/j.1365-2273.2002.00594.x
|View full text |Cite
|
Sign up to set email alerts
|

More siblings, less hay fever: more evidence

Abstract: The prevalence of allergic rhinitis is increasing. Many authors have noted the prevalence of hay fever is less in children from large families and the 'hygiene hypothesis' has been suggested as an explanation. We looked at the association of sibling number and other variables on the prevalence of hay fever and perennial rhinitis. From 26100 households selected at random, 34362 questionnaires were returned from individuals over 14 years of age; 19.3% had symptoms of hay fever and a further 6.0% had symptoms of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
(47 reference statements)
1
2
0
Order By: Relevance
“…Better hygiene or fewer respiratory infections, and possibly closer attention paid to milder symptoms when a first‐born child is concerned, may both partly explain this difference. Our finding is in accordance with other reports of lower occurrences of allergic diseases associated with the presence and number of siblings (35, 39, 41).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Better hygiene or fewer respiratory infections, and possibly closer attention paid to milder symptoms when a first‐born child is concerned, may both partly explain this difference. Our finding is in accordance with other reports of lower occurrences of allergic diseases associated with the presence and number of siblings (35, 39, 41).…”
Section: Discussionsupporting
confidence: 94%
“…In the German birth cohort study (MAS), IgE concentrations were found to increase up to the age of 10, with higher values in boys than in girls (34). Several other studies (35)(36)(37)(38), with one exception (39), have also found male gender to be associated with an increased risk of allergic diseases, and the cohort study from the Isle of Wight reported a similar gender difference for FAs (40), whereas a Swedish study reported higher prevalence of FA among girls (35). In our results this difference was apparent only in FA, but not in FHS.…”
Section: Discussionmentioning
confidence: 99%
“…The odds of having hay fever were less for individuals with two or more siblings. 17 Recall bias could have influenced the results. In a European cohort study, atopy, defined by prick tests to common aeroallergens, was less common among those from larger families.…”
Section: Evidence For and Against The Hygiene Hypothesismentioning
confidence: 99%